PW 2289 Injury risk assessment in schools in karachi, pakistan. (November 2018) - Khan, Uzma Rahim; Naeem, Rubaba; Zia, Nukhba
Abstract : Studies from low- income countries have shown that 7% of all childhood injuries occur in schools; however little is known about the injury hazards present in the school environment. The objective of this study was to develop and pilot injury risk assessment tool in the schools in Karachi. The study was conducted from March – June 2013. These risk observations in school environment were done by trained data collectors. The injury risk assessment was done in 107 schools. About a quarter (26%) of classrooms had broken furniture. In 50.9% of schools the playground surface was of concrete. About 28.3% schools had low height of corridor walls, while 60.4% schools had open wires in electrical switches. In 14.2% of schools there were cleaning chemicals in toilets within the reach of children. There were stray dogs within schools (22.4%). This was the first time that injury school environment risks tool was developed and piloted in the context of Pakistan. There was a significant burden of hazards present in the school environment representing an important opportunity for injury prevention.